La orientación en el ministerio de educación pública costarricense / Guidance and counseling at the ministry of public education in Costa Rica - Ureña Salazar, Viria (Universidad de Costa Rica, 2015)
Este documento presenta una breve reseña histórica del origen de la Orientación como servicio que se ofrece en las instituciones educativas, el marco legal que  lo sustenta, su organización y  modalidades de trabajo, entre otros elementos. Se incluyen también aspectos teóricos de la Orientación como disciplina, lo que permite contextualizar, por ejemplo, las modalidades de trabajo en escuelas y colegios. Se menciona el hecho de que la Orientación en el Ministerio de Educación Pública tiene un sustento legal, cumple la doble función de coadyuvar como asignatura en el desarrollo integral del estudiantado y desarrollar como servicio los procesos de orientación; tiene además definidos principios y propósitos, así como que las principales modalidades de intervención que utiliza son la Orientación Grupal, la individual y el asesoramiento. This paper presents a brief history of the Counseling origin and service offered in educational institutions, as well as the legal foundations. In addition, the organization and working modalities are presented, among other aspects. Theoretical issues of Counseling as a discipline are also included, which allow the contextualization of the different working modalities that are applied in educational institutions. The  conclusions that are mentioned include the fact that Counseling at the Ministry of Public Education has a legal support, and serves the double function of being offered as part of the efforts for students’ holistic development  and as a service that implements programs according to established objectives. In addition, the main modalities used are group counseling, individual counseling, and consultation, all based on defined principles and purposes.